The Diversity of Airborne Bacteria Over the Tibet Plateau Decreased by Taklimakan Dust - Fanli Xue; Zhongwei Huang; Xuefei Huo; Qingqing Dong; Zhengpeng Li; Qianqing Gu (Geophysical Research Letters)
Abstract Taklimakan dust is known to be transported over long distances to the Tibetan Plateau, significantly impacting its climates and ecosystems. However, information on how dust aerosols affect airborne microorganisms is still lacking. In the summer of 2019, we simultaneously collected air samples from the Tibetan Plateau (Ali) and the Taklimakan Desert (Minfeng and Tazhong) and analyzed them using high‐throughput DNA sequencing techniques. We found that the diversity of airborne bacteria decreased by 42.2% during dust events. Taklimakan dust contributed 85.4% ± 2.1% of airborne bacteria on the Plateau. Moreover, the potential pathogens and bacterial ice nuclei (IN) in the Plateau increased by 16.4% and 73.8%, respectively. Our study provides novel insights into the impact of dust‐coated bacteria on the climate and ecosystem across the Tibetan Plateau.